Age of First Exposure to Football Is Not Associated With Later-in-Life Cognitive or Mental Health Problems - Iverson, Grant L.; Caccese, Jaclyn B.; Merz, Zachary C.; Büttner, Fionn; Terry, Douglas P. (Frontiers in Neurology, 2021)
Background: The purpose of this study was to determine if earlier age of first exposure to football is associated with worse brain health in middle-aged and older adult men who played high school football. Methods: Men from the United States, aged 35 and older, who reported playing high school football, completed a customized, online health survey via the Amazon Mechanical Turk (mTurk) platform. Survey items included physical, psychological, and cognitive symptoms over the past week and over the past year, sports participation history (including age of first exposure to football), medical history, and concussion history. Participants also completed the Patient Health Questionnaire-8 (PHQ-8) and the British Columbia Post-Concussion Symptom Inventory (BC-PSI). Results: There were 186 men (age M=51.78, SD=10.93) who participated in high school football, and 87 (46.8%) reported football participation starting before the age of 12 and 99 (53.2%) reported football participation at or after the age of 12. Those who started playing football at an earlier age reported a greater number of lifetime concussions (M=1.95, SD=1.79) compared to those who started playing at age 12 or later (M=1.28, SD=1.52; U=3,257.5, p=.003). A similar proportion of men who played football before versus after the age of 12 reported a lifetime history of being prescribed medications for depression, anxiety, chronic pain, headaches, or memory problems. When comparing men who played football before versus after the age of 12, the groups did not differ significantly in their ratings of depression, anger, anxiety, headaches, migraines, neck or back pain, chronic pain, concentration problems, or memory problems over the past week or the past year. The two groups did not differ significantly in their ratings of current symptoms of depression (PHQ-8; U=4,187.0, p=.74) or post-concussion-like symptoms (BC-PSI; U=3,944.0, p=.53). Furthermore, there were no statistically significant correlations between the age of first exposure to football, as a continuous variable, and PHQ-8 or BC-PSI scores. Conclusion: This study adds to a rapidly growing body of literature suggesting that earlier age of first exposure to football is not associated with later-in-life brain health.